Antifungal activity in vitro of propolis solutions from Argentina against two plant pathogenic fungi: Didymella bryoniae and Rhizotocnia solani - Gallez, Liliana María (2014)
Didymella bryoniae (Auersw.) Rehm and Rhizoctonia solani Kühn cause some of the most destructive fungal plant diseases in the southern Pampas Region of Argentina. The gummy stem blight caused by D. bryoniae affects melon crops, damaging leaves and fruits (Fiori et al., 2000). R. solani is a well-known species complex which causes seedling death in several crops (Nicoletti et al., 1999). Chemical control of fungi has increased the productivity and quality of various crops, but abuse of chemical products has caused soil pollution and harmful effects on human beings (Fiori et al., 2000). The replacement of synthetic fungicides by natural products, particularly those which are of plant origin such as propolis, could present advantages such as efficacy and low toxicity (Agüero et al., 2010).